Counterfeit Luxuries: Does Moral Reasoning Strategy Influence Consumers’ Pursuit of Counterfeits? - Chen, Jie (Journal of business ethics, 2018)
Morality, in the context of luxury counterfeit goods, has been widely discussed in existing literature as having a strong association with decreased purchase intention. However, drawing on moral disengagement theory, we argue that individuals are motivated to justify their immoral behaviors through guilt avoidance, thus increasing counterfeit purchase intention. This research demonstrates that consumers’ desire to purchase counterfeit luxuries hinges on (one of) two types of moral reasoning strategies: moral rationalization and moral decoupling. The empirical results show that each strategy increases purchase intention, but respectively through moral judgment and perceived benefit. Implications for researchers and managers are discussed.